The physiological basis of leader-follower roles in the dyadic alternating tapping task - Tomyta, Kenta; Saito, Natsuki; Ohira, Hideki (Frontiers in Psychology, 2023)
Cooperative and collaborative behaviors are important concepts for co-creative communication. One of the key elements for these behaviors is the leader-follower roles in human communication. Leaders are those who maintain their own pace and rhythm, on the contrary, followers are those who follow the pace and rhythm of the other. Well-coordinated leader-follower roles would produce better cooperative and collaborative behaviors, which could promote co-creative communication. Here, to explore the physiological basis for the leader-follower roles, we conducted the dyadic alternating tapping task with electrocardiographic and electroencephalographic recordings. The task would be stable for modeling human communication in the laboratory because it includes timing control in tens of milliseconds and turn-taking. Given that human communications are complex and constantly fluctuating, this study estimated the degree of leader-follower with the state-space model. This model allowed us to calculate two parameters independently for estimating the degree of leader-follower of each participant: αSelf (degree of one's tap(n) was explained by one's tap(n-1)) and αPair (degree of one's tap(n) was explained by one's tap (n-1) and pair's tap (n-1)). The result showed heart rate synchronization in the group in which both participants had high αPair. Also, the high-frequency component of heart rate variability was positively correlated with αPair. EEG analyses suggested the deactivation of the mirror neuron system (increasing φ1) in the participants with higher αSelf than lower ones. The activation of the mirror neuron system (increasing φ2) was shown in the participants with lower αPair than higher ones. These data of physiological basis for leader-follower roles could be useful for the constructivist approach to co-creative communication.